Urban tourism space research methods: evolution and patterns - Liszewski, Stanisław (Turyzm/Tourism, 2014)
The author attempts to sum up research on urban tourism space conducted as a part of the tourism geography MA seminar at the University of Łódź. He checks and enhances the definition of tourism space and tests a method of analyzing the contents of guidebooks across time. He also defines the correlation between the range of forms of urban tourism space, changes to it as well as to population, and the past and the present functions of the city.